Before the Acheulean: The emergence of bifacial shaping at Kokiselei 6 (1.8 Ma), West Turkana, Kenya. Issue 159 (October 2021) - Duke, Hilary; Feibel, Craig; Harmand, Sonia
Abstract: We present new evidence for the emergence of biface shaping from Kokiselei 6 in the Kokiselei Site Complex (KS) in West Turkana, Kenya. This rich and well-preserved new site presents an opportunity to investigate the earliest development of biface shaping. The emergence of biface shaping in lithic technology is often used as evidence for increased and/or novel cognitive abilities that contrast prior hominins' flaking capacities. Yet, recent research reveals a story of gradual change over time in a variety of different flaking and shaping strategies. Here, we present preliminary excavation and lithic data from Kokiselei 6 that will be critical for future investigations of biface shaping emergence at KS. Kokiselei preserves the oldest known Acheulean lithic assemblage, Kokiselei 4 (1.76 Ma), as well as several older sites. Geochronological research shows that Kokiselei 6 stratigraphically underlies Kokiselei 4 and is the oldest site in the complex at 1.8 Ma. The Kokiselei 6 excavation yielded thousands of piece-plotted lithic artifacts and faunal remains. Preliminary analysis of the lithics ( n = 3856) indicates a prevalence of bifacial flaking strategies alongside minimal evidence for rough biface shaping. We argue that the flaking strategies observed from bifacial cores share similar operations and abilities as those involved in the production of the roughly shaped bifaces at the site. This preliminary evidence supports existing arguments that biface shaping emerged gradually out of variability in bifacial core reduction, ultimately leading to the systematic production of bifaces characteristic of the Acheulean. Future work teasing apart the processes of technological change at KS more broadly will be critical for understanding the emergence of biface shaping. These new data add to a growing narrative that opposes long-held assumptions about hominin cognitive evolution that suggest Acheulean technology required new, and more complex, cognitive abilities and gestures.